Peran Mahkamah Konstitusi dalam Penguatan Demokrasi Indonesia: Perspektif Kedaulatan Hukum dan Pembagian Kekuasaan - Arifin, Firdaus (CV. Social Politic Genius (SIGn), 2023)
This study aims to explore the crucial role of the Constitutional Court in upholding the Sovereignty of Law, maintaining the Distribution of Power, and strengthening democracy in Indonesia. This study uses a normative legal research method. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The results show that the Constitutional Court plays a central role in strengthening democracy through judicial review of laws, protection of human rights, oversight of the executive and legislative branches, and maintenance of the balance of power and social harmony. The Court also acts as a guide for just public policy and a guardian of social harmony within Indonesia’s legal pluralism. Therefore, it is recommended that the Constitutional Court continue to strengthen its role, enhance its dialogical approach with the public, and promote transparency in decision-making. The Government and Legislators need to pay attention to the principles of the Constitution, social justice, and human rights in formulating legislation and implementing Constitutional Court decisions with total commitment. The public is expected to monitor and demand the active implementation of constitutional court decisions. Collaboration among the Constitutional Court, the Government, Legislators, and the public is critical to realizing a democratic and just society in Indonesia.